Efficacy and safety of ciprofol for agitation and delirium in the ICU: A multicenter, single-blind, 3-arm parallel randomized controlled trial study protocol - Liu, Guo Liang; Wu, Guo Zhi; Ge, Dong; Zhou, Heng Jie; Cui, Song; Gao, Kai; Sun, Wei Jia; Yu, Dong Hai; Liu, Si Bo; Liu, Jin Jie (Frontiers in Medicine, 2023)
Background: Agitation is very common in the intensive care unit (ICU). The causes include pain, delirium, underlying disease, withdrawal syndrome, and some drug treatments. The practical goal of ICU treatment is to find an appropriate sedation regimen to reduce pain, restlessness, and delirium. Previous trials have examined the use of dexmedetomidine, but no trials have evaluated the efficacy and safety of ciprofol, a new sedative drug. Methods: This study was a multicenter, single-blind, 3-arm parallel randomized controlled trial. Intensive care unit (ICU) patients aged ≥18 years with agitation and delirium who met the eligibility criteria were included. The main outcome was the proportion of patients who needed additional study medication or midazolam due to agitation within 4 h after the first intravenous injection of the study medication. The secondary outcomes included the pass rate as indicated by a Richmond Agitation-Sedation Scale (RASS) score <+1, the effectiveness rate of improving delirium symptoms, the number of recurrences of agitation within 24 h, the incidence of rescue treatment, the dose and cost of analgesic and sedative drugs, the length and cost of ICU stay, and the 30-day survival period. The safety evaluation included the incidence of adverse events (hypotension, bradycardia, hypoxia, etc.) and the rate of endotracheal intubation. The subjects were randomly assigned to receive ciprofol, dexmedetomidine, or normal saline at a ratio of 1:1:1. The rates of additional drug administration within 4 hours after the first injection of the study drug in the three groups were 40%, 50%, and 90% respectively. A total sample size of 81 subjects was required to reach 90% power and an α of 0.05. Considering a 20% loss rate, 102 patients were enrolled and randomly assigned to the three groups in equal proportions. Ethics and communication: This trial was approved by the Ethics Committee of Dalian Municipal Central Hospital. The communication plan includes presentations at scientific conferences, scientific publications, and presentations to the public through nonprofessional media. Clinical Trial Registration: www.ClinicalTrials.gov, identifier: ChiCTR2200062799.